Usos e desusos da noção de vulnerabilidade na saúde pública no Brasil - Mota, Saulo Tavares da (2018)
The aim of this study is to analyze how Vulnerability emerged as a problem and an intervention object for Public Health policies in Brazil, and the ways it has been used by professionals of Primary Health Care in the city of São Paulo - SP. The notion of Vulnerability was adopted in Brazil by the Ministry of Health as one of the fundamental intervention objects of the National Health Promotion Policy (NHPP), producing profound changes in the way of defining, identifying, intervening and prioritizing the population to be served, producing changes in the practices of public health professionals and users in the country. As a research method, we start with the genealogy developed by Michel Foucault. As an analytical of the modes of subjectivity, the genealogy allowed us to glimpse the historical conditions of the production of knowledge, sets of rules and ways in which health professionals recognize situations of vulnerability and use this notion in their practices. The research was developed from the analysis of archives and documents of the field of Public Health policies, participant observation of activities by professionals carried out in Primary Health Care units, as well as interviews with such professionals. It was verified that the notion of vulnerability was not used to give meaning to a complex reality, but to a concrete action on the problems that it names and proposes. Historically different uses and strategic functions have been produced for the notion of vulnerability in Brazil amidst disputes, confrontations, transformations and resistances. If, on the one hand, the emergence of such a notion in the field of HIV/AIDS care in Brazil constituted resistance and problematization of the concept of health risk, on the other hand, its spread and its use in other public health fields suffered appropriations that acted out different strategic functions and moved away from the initial critical stance. The process of constitution of the notion of vulnerability as a problem and object of intervention in public health historically involved control strategies and resistance practices. In the quotidian of the practices of the professionals of the Primary Attention to Health of São Paulo articulate, on the one hand, strategies of governmentality through institutions, procedures, analyzes, calculations and tactics that allow establishing relations of power over the population, with the intention to make it useful and participative, through a neoliberal rationality, interested in increasing capacities and security strategies, controlling and avoiding risks. On the other hand, in this same context, the practices of recalcitrance move these strategies with resistances, oppositions, elusive, inversions of positions. Each actor seeks to affirm ways of living that are often inconsistent with preestablished performance guidelines. In agreement with Judith Butler, we understand that attention to the situation of violence and precariousness to which many people are exposed is fundamental, but it is also necessary to refuse policies that victimize or stigmatize these people with the argument of protection or salvation, so that they offer resources for their strengthening and empowering their ways of living